Solar-powered five-leg inverter-driven quasi-dynamic charging for a slow-moving vehicle - Shanmugam, Yuvaraja; Narayanamoorthi, R.; Vishnuram, Pradeep; Savio, Dominic; Yadav, Arvind; Bajaj, Mohit; Nauman, Ali; Khurshaid, Tahir; Kamel, Salah (Frontiers in Energy Research, 2023)
Road transport is becoming increasingly electric as it becomes more environmentally friendly. A green transportation system includes solar arrays along the roadside which is encouraging the eco-friendly EV charging system. This paper proposes the use of an installed photovoltaic system to charge the batteries of slow-moving electric vehicles using a five-leg inverter. The proposed 3.3 kW, 85 kHz inverter energizes the four transmitter pads, while a receiver pad moves over the transmitter pads and inductively extracts the power. The DC-DC converter is used to feed the power to the proposed inverter. The P and O-based MPPT algorithm with a tuned PI controller is used to generate the driving pulses of the DC-DC converter. The signals are generated based on the voltage and current output of the solar panel output. This control algorithm ensures the stability of the system output response. Additionally, the tuned DC-DC converter is used to achieve maximum efficiency independent of the load resistance. The transferred power is maintained constant concerning the variations of battery resistance. The power is transferred through a 520*520 mm Double D-pad, while the series-series compensation network assists the charging pads to achieve resonance. In the developed system, the nominal charging voltage and current are 143.5 V, 20 A with an equivalent battery resistance of 7.3 Ω.